A versatile mechanized setup for controlled experiments in archeology. Issue 1 (1st January 2020) - Calandra, Ivan; Gneisinger, Walter; Marreiros, João
ABSTRACT: Experimentation has always played an important role in archeology, in particular to create reference collections for use-wear studies. Different types of experiments can answer different questions; all types should therefore be combined to obtain a holistic view. In controlled experiments, some factors are tested, while the other factors are kept constant to improve the signal-to-noise ratio. Yet, controlled experiments have been conducted with variable degrees of control. Although they seem decoupled from archeological applications, mechanized experiments and the robust causal relationships they measure are critical to answer archeological questions like understanding the processes of use-wear formation. Here we introduce the concept behind using the SMARTTESTER®, a modular material tester, and we present four different setups (linear, rotary, percussion and oscillating) and their potential archeological applications. Such experiments will contribute to our understanding of causality in human tool use.